“You’ll never meet someone like me again”: Patty Jenkins’s Monster as Rogue Cinema - Wise, Michelle D. (Text Matters: A Journal of Literature, Theory and Culture, 2019)
Film is a powerful medium that can influence audience’s perceptions, values and ideals. As filmmaking evolved into a serious art form, it became a powerful tool for telling stories that require us to re-examine our ideology. While it remains popular to adapt a literary novel or text for the screen, filmmakers have more freedom to pick and choose the stories they want to tell. This freedom allows filmmakers to explore narratives that might otherwise go unheard, which include stories that feature marginal figures, such as serial killers, as sympathetic protagonists, which is what director Patty Jenkins achieves in her 2003 film Monster. Charlize Theron’s transformation into and performance as Aileen Wuornos, and Jenkins’s presentation of the subject matter, make this film an example of rogue cinema. In addition, Aileen Wuornos is portrayed as a clear example of the rogue character. This character trope frequently defies social standards, suffers from past trauma, is psychologically complex, and is often exiled. As a prostitute and social outcast, Aileen Wuornos exists on the fringes of society and rejects the hegemonic power structure and later heteronormativity of society, which makes her a rogue figure. While there are several aspects to consider when analyzing Jenkins’s film, my intention is to argue that this film is an example of rogue cinema because of its content. In order to accomplish this task, I examine Theron’s bodily transformation and her performance as Wuornos. Furthermore, I look at how Jenkins handles the depiction of romantic love and gendered violence and argue that her treatment of this content renders this film rogue.